The Model Legume Medicago Truncatula 2019
DOI: 10.1002/9781119409144.ch22
|View full text |Cite
|
Sign up to set email alerts
|

Genetic control of flowering time in legumes

Abstract: The timing of flowering, and in particular the degree to which it is responsive to the environment, is a key factor in the adaptation of a given species to various ecogeographic locations and agricultural practices. Flowering time variation has been documented in many crop legumes, and selection for specific variants has permitted significant expansion and improvement in cultivation, from prehistoric times to the present day. Recent advances in legume genomics have accelerated the process of gene identificatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
56
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(57 citation statements)
references
References 72 publications
1
56
0
Order By: Relevance
“…Flowering time is a model trait for understanding the genetics of clinal adaptation (Mouradov, Cremer, & Coupland, 2002;Pineiro & Coupland, 1998;Weller & Ortega, 2015), and the evolution of clines Caicedo, Stinchcombe, Olsen, Schmitt, & Purugganan, 2004;Samis, Heath, & Stinchcombe, 2008;Stinchcombe et al, 2004) and invaded range (Samis et al, 2012). In the model legume, Medicago truncatula, a dozen genes from several pathways involved in floral development are associated with clinal variation in flowering time (Burgarella et al, 2016).…”
Section: Candidate Genes Underlying Flowering Time Variationmentioning
confidence: 99%
“…Flowering time is a model trait for understanding the genetics of clinal adaptation (Mouradov, Cremer, & Coupland, 2002;Pineiro & Coupland, 1998;Weller & Ortega, 2015), and the evolution of clines Caicedo, Stinchcombe, Olsen, Schmitt, & Purugganan, 2004;Samis, Heath, & Stinchcombe, 2008;Stinchcombe et al, 2004) and invaded range (Samis et al, 2012). In the model legume, Medicago truncatula, a dozen genes from several pathways involved in floral development are associated with clinal variation in flowering time (Burgarella et al, 2016).…”
Section: Candidate Genes Underlying Flowering Time Variationmentioning
confidence: 99%
“…In our experiment, at the first time-point (TP1) under FR-enriched light, we found a gene-coding protein (TSub_g12538) homologous of a pea FTb2 whose relative expression was also higher under FR compared to B-enriched lights. This protein is expressed specifically in pea and Medicago leaves under long days and meets the characteristics of the classical ‘florigen’ (Weller & Ortega 2015). The differential expression of this homologous gene may suggest its role as a floral promoter in subterranean clover.…”
Section: Discussionmentioning
confidence: 93%
“…The floral promoter CO protein is up-regulated by long-day growing conditions and its expression is stabilised by FR light through PHYTOCHROME A activity (Kim et al 2008; Pin & Nilsson 2012; Song et al 2013). In Medicago, a temperate legume as subterranean clover, it has been suggested that the integration of responses to day length and light quality may not be regulated by CO -like ( COL ) genes (Wong et al 2014; Weller & Ortega 2015). In contrast, in subterranean clover, we identified the expression of a CCT motif ( TSub_g7401 ) at an early developmental stage (TP1) under FR-enriched light.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations